Nurse-Physician Communication Team Training in Virtual Reality Versus Live Simulations: Randomized Controlled Trial on Team Communication and Teamwork Attitudes - Liaw, Sok Ying; Ooi, Sim Win; Rusli, Khairul Dzakirin Bin; Lau, Tang Ching; Tam, Wilson Wai San; Chua, Wei Ling (JMIR Publications, 2020)
BackgroundInterprofessional team training is needed to improve nurse-physician communication skills that are lacking in clinical practice. Using simulations has proven to be an effective learning approach for team training. Yet, it has logistical constraints that call for the exploration of virtual environments in delivering team training. ObjectiveThis study aimed to evaluate a team training program using virtual reality vs conventional live simulations on medical and nursing students' communication skill performances and teamwork attitudes. MethodsIn June 2018, the authors implemented nurse-physician communication team training using communication tools. A randomized controlled trial study was conducted with 120 undergraduate medical and nursing students who were randomly assigned to undertake team training using virtual reality or live simulations. The participants from both groups were tested on their communication performances through team-based simulation assessments. Their teamwork attitudes were evaluated using interprofessional attitude surveys that were administered before, immediately after, and 2 months after the study interventions. ResultsThe team-based simulation assessment revealed no significant differences in the communication performance posttest scores (P=.29) between the virtual and simulation groups. Both groups reported significant increases in the interprofessional attitudes posttest scores from the baseline scores, with no significant differences found between the groups over the 3 time points. ConclusionsOur study outcomes did not show an inferiority of team training using virtual reality when compared with live simulations, which supports the potential use of virtual reality to substitute conventional simulations for communication team training. Future studies can leverage the use of artificial intelligence technology in virtual reality to replace costly human-controlled facilitators to achieve better scalability and sustainability of team-based training in interprofessional education. Trial RegistrationClinicalTrials.gov NCT04330924; https://clinicaltrials.gov/ct2/show/NCT04330924